PRIVILEGE OF READING INTENSIVELY AND THE BETTERMENT OF IT IN TARGET LANGUAGE THOUGH TASK-BASED METHOD OF TEACHING - Mirsalixova Robiya (Journal of new century innovations, 2024)
Annotation: The purpose of article is to accent on intensive reading through Task-based method of teaching a foreign language. Additionally, privileges and the benefits which come from reading intensively as well as the ways for improvement this skill are also provided.